2011
DOI: 10.1504/ijise.2011.042540
|View full text |Cite
|
Sign up to set email alerts
|

Hand anthropometric survey of male industrial workers of Haryana state (India)

Abstract: A survey has been conducted to create a database of hand anthropometric dimensions of 878 male industrial workers from medium and small enterprises of Haryana state of India. A set of selected 37 right-hand anthropometric dimensions are measured using the techniques as per the guidelines in NASA -1024NASA - (1978. This database will be useful for new designs/design modifications of hand tools, work stations, hand apparel, protective equipments, etc. Primary data collected in the study have been used to comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Hand anthropometric data are taken based on standard adaptation provisions from Chandra et al (2011) and dimensions according to Purnomo (2014). Hand anthropometric measurements were taken directly using calipers, roll metline, and 3D printed cone.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Hand anthropometric data are taken based on standard adaptation provisions from Chandra et al (2011) and dimensions according to Purnomo (2014). Hand anthropometric measurements were taken directly using calipers, roll metline, and 3D printed cone.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Abbas et al, 35 from the analysis of the torque data of repetitive passive wrist movements, found that the mean of the torques for slow ( approximately 6° s −1 ) and moderate (approximately 120° s −1 ) angular velocities are, respectively, 0.056 and 0.062 Nm for healthy subjects and are 0.11 and 0.15 Nm to hemiplegic patients. The hand dimensions were studied, for example, by Chandra et al 36 and found the breadth mean of the hand was 102.36 ± 4.85 mm and the length mean of the hand was 187.06 ± 8.62 mm. By Plagenhoef et al, 37 the average mass of a human forearm and hand is approximately 2.295% of the total body mass.…”
Section: Wrist Kinesiology and Spasticitymentioning
confidence: 99%
“…The sizes or dimensions of hand are important in any consideration of hand function [6]. Handles of tools or objects to be handled by hand must be suitably sized.…”
Section: B Anthropometric Studymentioning
confidence: 99%